O sertão no arquivo: considerações sobre o(s) regionalismo(s) na literatura brasileira - Viviane Cristina Oliveira (2021)
Regionalism, a concept which crosses different moments in the history of Brazilian literature, it is the main theme of this research, constituted in the transits between fictional, theoretical texts and archival documents. They are the collections of Mário Palmério, Bernardo Élis and João Guimarães Rosa spaces from which we make some considerations about regionalism as a word inscribed in notes, essays and newspaper clippings, a word that the writers read in different ways in a search for the meanings of them which gave us the opportunity for multiple interpretations. Interpretations that we rehearsed from what they wrote on the topic, as well as from the links between the authors' works and archival practices, such as the composition of lists, inventories, catalogs and genealogies, figured in fiction and noticeable in their respective collections. Such practices, which may be associated with an excess of local data that made the fortune and misfortune from many authors named regionalists, allowed us to figure out a certain dialogue between these writers who published their most recognized texts in 1956: O tronco, by Bernardo Élis, Vila dos Confins, by Mário Palmério, Grande sertão: veredas and Corpo de baile, by Guimarães Rosa. Contemporary, although distanced over time by literary criticism, the two writers from Minas Gerais and the writer from Goiás allowed us, when gathered together, rediscover regionalism in their variations, their contradictions, their unfinished similar to that of the files, in their potentiality of concept which survives, in the sense of survival read and studied by Aby Warburg, it survives as a nuisance and a meaningful challenge for our time.